Design Transformation of The Industrial Relations Peace : Towards A Prosperous, Harmonious and Fair Work Relations Model In The Karawang Industry - Fachmie Fardan Trikora Putra; Neneng Nurlaela Arief (PT. Publikasiku Academic Solution, 2024)
The minimum wage is one of the national strategic policies whose regulations are determined by the central government through laws and derivative regulations. The business problem faced by business actors in Karawang is the disruption of business operations due to the freeze that occurred during the minimum wage period at the district level. Even though discovery is a right as an Indonesian citizen, this research aims to initiate an industrial relations peace strategy for companies in Karawang to be able to carry out promotional, preventive, overcoming, and rehabilitative steps. This research focuses on the period 2019–2024 and analyzes the district minimum wage policy, which is accommodated by the Apindo Karawang Regency Leadership Council. The research methods used include literature studies, policy analysis, and interviews with relevant stakeholders such as business leaders, human resources managers, Government and Union Leaders . The results of the analysis highlight significant developments in the industrial relations paradigm in Karawang by identifying factors that influence welfare, harmony, and justice in work relations. The findings of this research provide in-depth insight into the impact of implementing minimum wages on the dynamics of industrial relations in companies in Karawang. This research provides a positive contribution to business as well as a better understanding of the strategies that can be used to achieve prosperous, harmonious, and fair working relationships in an industrial environment. It is hoped that the policy implications resulting from this thesis can provide guidance for stakeholders in developing steps that support the positive development of industrial relations in Karawang.